Avaliação de estratégias de controle adaptativo do gerador síncrono de ímã permanente aplicado em sistema de energia eólica - Pena, Danilo de Santana (Universidade Federal Rural do Semi-Árido, 2015)
The objective of this study is to evaluate different strategies for adaptive control in order to contribute to better performance controllers with synchronous generators with uncertainties of the parameters or disturbances. The permanent magnet synchronous generators are growing in the market for wind power generation, this being the necessary motivation for choosing this plant. A study and analysis of subsystems of wind energy conversion are performed, and the model of the wind turbine, the mechanical transmission system and synchronous generator are described. The project strategy with conventional control is performed and will be the target of comparison for the implemented adaptive control strategies
Evaluation of adaptive control strategies of permanent magnet synchronous generator applied in wind power system
Keywords: Adaptive control; PMSG; Wind energy; Wind turbine; Controle adaptativo, gerador síncrono, energia eólica, turbina eólica; ENGENHARIAS::ENGENHARIA ELETRICA